2002
DOI: 10.1136/jnnp.72.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and neurocognitive outcome from coronary artery surgery

Abstract: The apolipoprotein E (apoE) gene (APOE) is polymorphic with three alleles, e2, e3, and e4, which give rise to three isoforms, E2, E3 and E4. Many reports have now described a strong association between the e4 allele and risk of developing late onset Alzheimer's disease as the result of the E4 isoform binding to β-amyloid protein and accelerating the deposition of amyloid, which is the main constituent of senile plaques. 1 The APOE e4 allele also appears to be associated with deposition of β-amyloid after trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…One possible reason is because there are substantial aging effects on the cognitive domain of memory that are not shared with the effect of age on general cognition (Salthouse & Ferrer-Caja, 2003). However, in addition to memory, APOE status might influence verbal reasoning , verbal fluency (Robson et al, 2002), and visual attention (Greenwood, Sunderland, Friz, & Parasuraman, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason is because there are substantial aging effects on the cognitive domain of memory that are not shared with the effect of age on general cognition (Salthouse & Ferrer-Caja, 2003). However, in addition to memory, APOE status might influence verbal reasoning , verbal fluency (Robson et al, 2002), and visual attention (Greenwood, Sunderland, Friz, & Parasuraman, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Possession of the 4 allele of the APOE gene is associated with earlier death and increased risk of cardiovascular disease, stroke, and Alzheimer's dementia (Farrer et al, 1997;Smith, 2002). The APOE gene is associated with mild cognitive impairment (DeCarli et al, 2001) and perhaps with cognitive decline after head injury (Samatovicz, 2000), cardiac bypass surgery (Robson et al, 2002), and diabetes (Ferguson et al, 2003).…”
mentioning
confidence: 99%
“…48 Data are inconsistent regarding the role of the apolipoprotein ε4 genotype in perioperative cerebral injury. 2,4,43,87,91,94 Other investigators have examined for a relationship between polymorphisms of genes involved in pathways regulating coagulation, cell adhesion, and inflammation with perioperative cerebral injury. Grocott et al 39 found that the combination of 2 minor alleles of C-reactive protein (CRP; 3′UTR 1846C/T) and interleukin-6 (IL-6; -174G/C) were significantly associated with stroke after cardiac surgery (odds ratio, 3.3; 95% CI, 1.4 to 8.1; P=0.0023).…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…The association between these SNPs and cognitive impairment was tested six months after surgery by multiple logistic regression adjusted by age, education, basal cognitive level and populational structure. A significant Steed et al [15] Robson et al [16] Askar et al [17] Lelis et al [13] Tagarakis et al [12] Arrowsmith et al [61] Roach et al [59] Mitchell et al [62] Wang et al [60] relationship was obtained among carriers of lower alleles of CRP and a reduction of risk for CD (Odds Ratio = 0.37; 95%CI: 0.16 -0.78; p-value = 0.013). In carriers of these lower alleles, the pre-operative levels of CRP were lower, ratifying biological support for the observed allelic association.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…and postoperative (temperature) [1]. Additionally, some researchers have reported a genetic influence on the surgical outcome, in particular related to the presence of the apolipoprotein E å4 allele [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%